2011
DOI: 10.1111/j.1365-2621.2011.02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides prepared by acid hydrolysis of polysaccharides from pumpkin (Cucurbita moschata) pulp and their prebiotic activities

Abstract: As a rich source of polysaccharides, pumpkin pulp was used for the production of oligosaccharides. To investigate the prebiotic potential of the oligosaccharides, prepared by acid hydrolysis of polysaccharides from pumpkin pulp, the effect of the oligosaccharides on lactobacilli growth was studied. The oligosaccharides were composed of galactose (99.03%) and glucose (0.97%). The molecular weight distribution of the oligosaccharides showed a larger part of low molecular weight fraction in a range from 5000 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
2
20
1
1
Order By: Relevance
“…Apart from available oligosaccharides, hydrolytic or synthetic methods also allow obtaining low molecular weight carbohydrates. Most oligosaccharides used as prebiotics at present are produced by extraction from natural sources, obtained by the enzymatic or acid hydrolysis of polysaccharides, or produced by enzymatic transglycosylation (Du et al ., ). Low molecular weight FOS can be enzymatically synthesised from sucrose.…”
Section: Oligosaccharide Productionmentioning
confidence: 97%
See 2 more Smart Citations
“…Apart from available oligosaccharides, hydrolytic or synthetic methods also allow obtaining low molecular weight carbohydrates. Most oligosaccharides used as prebiotics at present are produced by extraction from natural sources, obtained by the enzymatic or acid hydrolysis of polysaccharides, or produced by enzymatic transglycosylation (Du et al ., ). Low molecular weight FOS can be enzymatically synthesised from sucrose.…”
Section: Oligosaccharide Productionmentioning
confidence: 97%
“…The production of oligosaccharides by hydrolysis usually requires the extraction of polysaccharides from the raw material, followed by depolymerisation (Du et al ., ). FOS and XOS are most commonly produced by hydrolysis of polysaccharides, which can be caused by chemical, enzymatic, or physical agents.…”
Section: Oligosaccharide Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…Iz tog razloga, pojedinim naučnicima polisaharidi bundeve poslužili su kao dobar supstrat za proizvodnju oligosaharida primenom kisele sredine. Du i saradnici [26] pokazali su značajnu probiotsku aktivnost ovako nastalih oligosaharida. Naime, in vitro testom je pokazano da je broj bakterija Lactobacillus delbrucckii u kulturi bio značajno veći nakon suplementacije ovim jedinjenjima u odnosu na kontrolu.…”
Section: Biološka Aktivnost Polisaharida Bundeveunclassified
“…Recent studies demonstrated that natural polysaccharides exhibiting their physiological functions by oral administration to animals are correlated to the oligosaccharide derivatives produced by gastric acid or enzymes in digestive tract (Beveridge, & Richards, 1973;Agbagla-Dohnani, Cornu, & Broudiscou, 2012). It is well known that treatment of polysaccharide with acid hydrolysis can interrupt the polymer chain, generating the less molecular mass of carbohydrates (oligosaccharides) (Du, Song, Hu, Liao, Ni, & Li, 2011). The produced oligosaccharides exhibited improving physiological activities in contrast with their initial polysaccharides because they are easier to be absorbed into blood circulations and have higher bioavailability in organisms (Al Jamal, Roughley, & Ludwig, 2001;Juskiewicz, Zdunczyk, Jankowski, Krol, & Milala, 2008).…”
Section: Introductionmentioning
confidence: 99%